Transformasi Media Pembelajaran Di Masa Pandemi Covid-19 - Susilawati Susi; Muhamad Yasir (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The purpose of this community service activity is to provide information to the community of Choblong Cibeureum Cisarua Bogor village about a wide variety of learning media that can be used during distance learning activities (learning from home). The target of community service is the community in Cibeureum Cisarua, Bogor. Partner problems can be resolved through three stages: preparation, implementation, and evaluation. Preparation was made by conducting a preliminary survey to see conditions in the field regarding distance learning during the Covid-19 pandemic. Implementation is carried out by counseling, using the lecture method, namely the presentation technique, followed by a question and answer discussion and training to open links to free online learning providers as an attractive online-based learning medium. Activity evaluation is carried out for each stage by collecting and summarizing data from each activity stage. The results of the training activities show the level of success with an indication of a positive response from the participants, and most (75%) of the participants have understood how to open links for online learning providers. Keywords: media, learning, online, distance